ʺInternet technologies as a means of students’ independent work intensification in the process of learning english in Higher Education Institutionsʺ - Monastyryova, L.; Pavlova, O. (Problems of Engineer-Pedagogical Education, 2022)
The article deals with the intensification of students' independent work in the process of learning English by means of Internet technologies. The article notes that while planning students' independent work, it is necessary to take into consideration the leading methodological approach, which is grounded in methodological literature: during independent work, the main function of education is realized, which is the consolidation of knowledge and its transformation into sustainable abilities and skills. It is noted that in today's reality, the purpose of independent work should also include the search for and acquisition of new knowledge, including the use of modern information technologies. The author notes that the main task of any higher education institution is to prepare specialists for independent practical activity. The learning process in higher education today is based on the independent and creative activity of students. Independent work is a type of learning activity, which is carried out by students in the classroom, both under the guidance of the teacher, and without direct guidance from the teacher during independent training and participation in various extracurricular activities. The article points out that the use of Internet resources as well as networking in teaching English in higher education are effective in different types of implementation in the educational process, but with the aim of intensifying students' independent work the following things are important: integration of authentic Internet materials into the context of the class; students' independent work, the purpose of which is to find information within their future profession, independent work with informational materials in English, including their search, comparison and selection; ability to critically analyze and summarize information obtained from foreign media; development of discursive skills as well as skills of argumentative speech and public speaking. The work emphasizes that the use and integration of Internet technologies in the educational process of higher education institutions contribute to the effective solution of the following practical tasks: development of foreign language reading skills and abilities using materials of varying degrees of complexity; improvement of listening skills based on authentic audio texts as well as texts prepared by the teacher; enhancement of writing skills, updating the vocabulary of the modern English language; formation of sustainable motivation for students’ foreign language activity in the classroom based on the systematic use of really relevant materials.